Nutrition Knowledge and Food Frequency Among People with Diabetes Mellitus - Putri, Santy Irene; Pratamaningtyas, Susanti; Fajriah, Asruria Sani; Widiyanto, Aris (Journal of Local Therapy, 2024)
Diabetes Mellitus is one of the chronic diseases that causes the highest death in Indonesia. In fact, the number of cases of pain continues to increase. Riskesdas 2018 data shows that the total number of diabetes cases in Indonesia is 8.5%. Complications include heart attacks and strokes, severe leg infections (causing gangrene, which may result in amputation), end-stage renal failure, and sexual dysfunction. After 10-15 years from the time of diagnosis, the prevalence of all complications of diabetes increases markedly. Efforts that can be made to prevent diabetes mellitus are managing lifestyle, regular physical activity, maintaining diet, and conducting early examinations. The purpose of this study was to determine the relationship between nutrition knowledge and food frequency with the incidence of diabetes mellitus. This was an observational analytic study with a cross-sectional study design conducted in Malang. A sample of 54 people was selected by purposive sampling technique. The dependent variable is the incidence of diabetes mellitus. Independent variables include nutrition knowledge and food frequency. The data were collected by questionnaire and analyzed using Pearson correlation. Nutrition knowledge (r = 0.40; p = 0.003) and food frequency (r = 0.33; p = 0.017) related to diabetes mellitus and statistically significant. Good nutritional knowledge and regular food frequency can prevent diabetes mellitus.